Perancangan Interior Pusat Informasi Gizi Anak di Surabaya - Grace Mulyono, Christien Dea Andriani (Intra, 2014)
The health development of nowadays children is far different from children in the past. Children that are born in this modern era have bigger potential to suffer from the diseases that were once only suffered by adults such as obesity, diabetes, and stroke. The supporting factor are the diet of nowadays instant lifestyle and the limited activities which occur due to the technology development. The design ofÂ Childrens Nutrient Information Center is one of the ways to help parents and especially children to introduce the healthy food and also to help them to learn cooking by providing food adventure center facility, cooking studio, library, and consultation room. The design concept is Healthy Spoon which aimed for a reminder to the children of the importance of eating healthy food through each spoon they eat form.Â